¿Qué pasa por el cuerpo en la depresión? (2009)
ABSTRACT: The question for the status of the body has been a constant on the studies about depression, especially when its etiology and its symptomatic manifestations are examined. The body is the focus of the research “Experiences that help people feel better with the experience of depression”; but there its significance encompasses more than its organic characteristics, it is accounted also as an important element for the understanding of the phenomenology, diagnosis, evolution, treatment, and improvements of depression. The body is considered from diverse perspectives by those interviewed in the research and also by the different theoretical perspectives. The body can be understood as an organism or as a symbolic construct, and this has repercussions for the meanings and interpretations that can be formed around the psychosomatics of depression.